Does economic development mitigate tax evasion? evidence from evasional Kuznet curve - Tan, Yan Ling; Habibullah, Muzafar Shah; Din, Badariah (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Tax evasion is a common problem persisted in all countries around the world. Recent estimates registered a loss of tax revenue amounting to US$3.1 trillion or 5.1% of world’s GDP. Tax revenue losses have negative consequences to the government ability to fueled economic growth by providing enough public infrastructure and other services. In this study we have estimated the share of shadow economy to the official economy for Malaysia for the period 1983 to 2013 based on Tanzi-type currency demand approach (CDA) that captures all relevant determinants of the shadow economy. We employ the nonlinear autoregressive distributed lag (NARDL) modeling approach proposed by Shin, Yu and Greenwood-Nimmo (2014) which gives more merits over linear ARDL approach. Given the estimated size of the shadow economy, we are able to calculate the loss in tax revenue as a result of the presence of the shadow economy. We further analyze factors determining tax evasion in Malaysia. Our results suggest that tax evasion exhibit an inverted-U shape curve (nonlinear) with the level of economic development and positive relationship with various measures of tax burden in Malaysia during the period under study. We conclude that increasing the level of economic development able to reduce tax evasion in Malaysia.